Vitreous Cyst: A Case Report - Usman Imtiaz, Farukh Jameel, Hussain Ahmad Khaqan (Pakistan Journal of Ophthalmology, 2015)
Vitreous cysts represent a very rare ocular malformation. These cysts can occur in an otherwise healthy eye or in a diseased eye or they can occur in association with the remnants of hyaloid system. We report here a case of a 14-year-old male presenting to us with complaint of painless transient blurring of vision in left eye. Visual acuity was 6/6 in right eye and 6/24 in left eye, which improved to 6/6 once the transient blurring goes away. On examination of the left eye, there was a freely floating cyst in the vitreous. It was translucent, with a smooth, brownpigmented surface. Rest of the examination was unremarkable. Blood tests including serology were normal. Periodic observation was recommended without any treatment. Key Words: Vitreous Cyst, Visual Acuity, Hyaloid System